Decoding the message: understanding soldiers' mutiny in Nigeria's counterinsurgency fight. (17th November 2022) - Ikem, Patrick Afamefune; Onuoha, Freedom C.; Edeh, Herbert C.; Ononogbu, Olihe A.; Enyiazu, Chukwuemeka
ABSTRACT: Since the commencement of the counterinsurgency fight against Boko Haram, the Nigerian Army has been faced with internal crises, such as corruption, poor welfare conditions for soldiers, among others, which have undermined efforts at defeating the insurgents. Military authorities have both down-played and denied these internal challenges. The result is frequent mutiny by soldiers. This paper examines the drivers, dynamics, and responses to mutiny within the Nigeria Army in the context of ongoing counterinsurgency (COIN) operation in the northeast. Anchored on the analytical framework of Tactical Communication Strategy, the paper contends that resort to mutiny is a strategy by soldiers to open up dialogue with the military authority and communicate to the public the internal factors that account for battlefield failures. Hence, the paper recommends that soldiers' welfare be given high priority rather than resort to punitive measures.